Oxytocin and the microbiome. (August 2021) - Erdman, Susan E.
Abstract: The equilibrium between host animals and their microbiota has been convincingly linked with overall host health. Numerous reports describe beneficial effects of probiotic microbiota on the health of humans and other species extending to improved immune functions, wound repair capacity, metabolism, and psychiatry. Among candidate unifying host effector molecules is oxytocin, a neuropeptide hormone related to sociability and a sense of physical and mental well-being. It has been shown in mouse models that endogenous oxytocin levels are upregulated after consuming the probiotic Lactobacillus reuteri derived from human breast milk, with interesting evolutionary implications. Using heirloom microbiota such as L. reuteri to naturally upregulate host endogenous oxytocin levels potentially overcomes the known therapeutic challenges of oxytocin's short half-life and obscure brain targets. Highlights: Microbiota are convincingly linked with human health, including immune functions, wound repair, metabolism and psychiatry. L. reuteri bacteria from human breast milk up-regulate a neuropeptide hormone oxytocin, related to sociability and well being. Supplemental oxytocin has been proposed to treat human health issues ranging from obesity to autism spectrum disorder. Using microbes to boost host endogenous oxytocin levels may overcome therapeutic obstacles of exogenous oxytocin treatments.